Comparison of laparoendoscopic single-site (LESS) surgery and conventional multiport laparoscopic (CMPL) surgery for hysterectomy: long-term outcomes of abdominal incisional scar. (17th February 2020) - Demirayak, Gökhan; Özdemir, İsa Aykut and Comba, Cihan and Aslan Çetin, Berna and Aydogan Mathyk, Begüm and Yıldız, Mustafa and Mihmanlı, Veli and Karaca, İbrahim and Öztürk, Mustafa and Güralp, Onur
Abstract: There is scarcity of data about the long-term results such as port-site hernia, body image scale and cosmesis scale outcomes between laparoendoscopic single-site (LESS) surgery and conventional multiport laparoscopy (CMPL) for hysterectomy. Eighty women, who underwent total hysterectomy by the LESS ( n = 40) and CMPL ( n = 40) technique due to benign and malign gynecological disorders, were evaluated with a cosmesis and body image questionnaire in an age-matched cohort study. Median follow-up time was 25 (6–30) months in both groups. The mean age of the patients was 49.3 ± 6.3 years. The mean body image scale scores were 5.3 ± 0.6 and 5.5 ± 1.2 in the LESS and CMPL groups, respectively ( p = 0.268). The mean cosmesis and scar scale scores were significantly higher in the LESS group compared to the CMPL group ( p = .011 and p < .001, respectively). Port-site hernia was detected in two patients in the LESS group, but not in the CMPL group. There was no cuff dehiscence in the LESS nor in the CMPL group. The LESS technique provides better cosmesis when compared with the CMPL technique. The body image perceptions in the two groups were similar. Women who wish to undergo the LESS surgery should be informed about the risk of incisional hernia. Impact statement: What is already known on this subject? Short-term results of LESS hysterectomy such as complication rates, additional port requirement, conversion to CMPL or laparotomy, pain score and analgesic use were evaluated in various studies. Several studies have been published on the safety and efficacy of single-port laparoscopic hysterectomy (LH); however, it has been unclear whether single-port LH offers benefits over multiport LH regarding long-term patient satisfaction and cosmetic satisfaction. What do the results of this study add? In this prospective cohort study, we aimed to compare long-term results (at least six months) of abdominal incisional scar between LESS and CMPL surgery for hysterectomy. The LESS technique provides better cosmesis when compared with the CMPL technique, although, the body image perceptions in the two groups were similar. What are the implications of these findings for clinical practice and/or further research? LESS technique can be offered as an option for hysterectomy since it provides better long-term cosmesis compared to CMPL.